Designing a Food Menu Catalog at a Web-Based Tonga Coffee Shop - Daeli, Cosmas Samuel; Hulu, Delisman (Pascal: Journal of Computer Science and Informatics, 2024)
The development of science and technology, especially computer technology, has grown rapidly and has had a significant impact in various fields such as offices, education, and others. Computers as a data processing tool have become an important element in supporting operations in various sectors. An organization or company needs competent human resources to realize its goals, including in achieving business profits. These human resources play a role in executing the main tasks of the organization or company. However, the processing of food menu sales catalogs that are still carried out manually by employees often causes errors in the delivery of menu details, leading to errors in processing consumer orders. In addition, the control of available food and beverage stocks is also not optimal, and there are difficulties in making food and beverage order transaction reports, resulting in unclear details of consumer visits. To overcome this problem, a web-based food menu catalog system was designed at the Tonga Coffee Shop. This system aims to facilitate the explanation of the Tonga Coffee menu to consumers, improve work efficiency in the Tonga Coffee Shop environment, and introduce food menus to the community, especially in the city of Medan. It is hoped that with this application system, the work process will become easier, the performance of employees in serving customers will increase, and the introduction of food menus at Tonga Coffee Shop will be more effective.